Glaciers in the Russian Mountains (Caucasus, Altai, Kamchatka) in the First Quarter of the 21st Century - V. M. Kotlyakov; T. Y. Khromova; G. A. Nosenko; A. Y. Muraviev; S. A. Nikitin (Лëд и снег, 2023)
The conducted studies allowed us to obtain a detailed picture of glaciation changes in the mountain regions of Russia, most provided with information about glaciers in the twentieth century. For the Caucasus glaciation, the data were obtained for the time periods 1911, 1952, 2000, 2014, 2018 and 2020; for Altai – for 1850, 1952, 2003 and 2018. For large glaciation nodes of the Central Altai – Katun, South and North Chuya Ridges additionally for 1968, 2008, and 2017. In both areas, a decrease in the area of glaciers since the beginning of the twentieth century and acceleration of the rate of reduction in the early twenty-first century have been revealed. The glaciers of the Caucasus and Altai reduced their size during this time by 46% and 48%, respectively. On average, in the twentieth century the glaciers of the Caucasus lost about 0.2% of the area per year, in the Altai – 0.15%, and in the early twentieth century 1.15 and 1.7% respectively. To study Kamchatka glaciers, we used data from the Glacier Inventory of the USSR (1950/1957) and images from different satellites in the period 2007–2019. The glaciers that were not previously registered in the Glacier Inventory of the USSR were identified. The greatest number of such glaciers is in the northern part of the Midnight Ridge, where out of 465 glaciers identified on modern satellite images, 216 were not included in the Glacier Inventory of the USSR. The area of glaciation in different regions of Kamchatka has changed extremely unevenly since the first cataloguing, which is associated with significant differences in glacier morphology. Glaciers of volcanic areas increased their size or remained stationary; here there is no tendency for glaciers to decrease due to the thick surface moraine consisting of volcanogenic material. Comparison of data from the Glacier Inventory of the USSR (as of the 1950s–70s) and the Glacier Inventory of Russia (2017–2019) shows a decrease in glaciation area from the mid-20th century to the end of the second decade of the 21st century in all mountainous regions of Russia except only the volcanic regions of Kamchatka. The area reduction ranges from 63% (Ural) to 13% (Kodar). The largest glacial systems of the Caucasus, Kamchatka and Altai have reduced their areas by 25, 22 and 39%, respectively.